EFEKTIVITAS MINUMAN KOMBINASI JAHE DAN LEMON UNTUK MENGURANGI EMESIS GRAVIDARUM PADA IBU HAMIL TRIMESTER I TAHUN 2024 - Julianti, Neneng Neneng Julianti; Jiehad, Niesha Rahmalia; Rosdiana, Novi Novita (Jurnal Delima Harapan, 2025)
Background: Emesis gravidarum is a symptom that is mostly in pregnant women, at 80% of pramides and 60% of multigravida. According to data from the Word Health Organisation, the incidence of emesis gravidarum is 14% of all pregnant women in the world. in Indonesia in 2021 as much as 67.9%. Ginger is a rhizome plant that is known to have a variety of benefits. It contains active compounds such as zingiberene essential oil (zingirone), gingerol, zingiberol, curcumin, fellandrene, bisabolene, vitamin A, and bitter resins that play a role in inhibiting serotonin. While lemons contain this compound, they also function to control cyclooxygenase (COX) I and II enzymes, inhibit the activity of prostaglandins, and help reduce pain complaints including nausea. Objective: To determine the effect of giving ginger and lemon combination drinks in pregnant women in the first trimester at TPMB Midwife Khaeni Nurkhaeni, A.M.Keb. Methods: This study uses a quantitative method, a design that uses a Quasi Experiment with a One Group Approach. The population of this study is all pregnant women in the 1st Trimester who experience Emesis Gravidarum, the sample in this study is 34 people, the research data collection technique is Totral sampling, the instrument used in this study is a questionnaire. Results: There was an effect of giving a combination of ginger and lemon to reduce Emesis Gravidarum in pregnant women in the first trimester with a value of <0.000 (p<0.05). Conclusion: in this study there is an effect to reduce emesis gravidarum in pregnant women in the 1st trimester and there is a difference before and after the administration of a combination of ginger and lemon in pregnant women in the 1st trimester. It is hoped that the results of this study can increase knowledge and insight about the benefits and be able to apply a combination of ginger and lemon drinks in the event of emesis gravidarum and become one of the innovations in the field of obstetrics.